Dinamika Identitas Kewarganegaraan Dalam Konteks Globalisasi: Studi Kasus Di Era Digital - Tita Ester; Bintang Auliya Tyananda; Ryan Dwi Prayoga; Dela Amelia; Eni Lutviana Fadila; Naifa Adelia (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Globalization is a modern development that has influenced the emergence of various possibilities to change the world. The impact of globalization has the potential to make the world more open and remove the barriers that make us need each other. This research aims to reveal the dynamics of citizenship identity in the context of globalization. Over time, the term "global citizenship" has become known, where values will be discussed that are in accordance with national identity which are used as benchmarks to face the era of globalization. It is through this that the young generation is able to make the values of national identity a basic direction with positive value in their efforts to face the current flow of globalization in the current digital era.